2022
DOI: 10.24235/eltecho.v7i1.10204
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Efl Learners’ Speaking Anxiety Through Selective Error Correction and Group-Work Strategies

Abstract: This quantitative study aimed to examine the level of speaking anxiety experienced by second-year high-school Acehnese EFL learners in their oral performance in L2 classroom and to investigate the attempt to lower their anxiety through the implementation of selective error correction and group work. The Foreign Language Speaking Anxiety Scale (Horwitz et al., 1986) was used as a means to survey and evaluate the learners" speaking anxiety, and their oral performance was assessed through speaking performance rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…Similar findings were obtained from studies conducted byAkkakoson (2016), Azizifar & Fariadian (2015), and Toubot et al (2018), Asysyifa et al (2019), Çağatay (2015) and Zulfikar (2022). Accordingto Toubot et al (2018), teaching methods and classroom atmosphere could be the reasons contributing to this finding.…”
Section: Levels Of Foreign Language Speaking Anxietysupporting
confidence: 87%
“…Similar findings were obtained from studies conducted byAkkakoson (2016), Azizifar & Fariadian (2015), and Toubot et al (2018), Asysyifa et al (2019), Çağatay (2015) and Zulfikar (2022). Accordingto Toubot et al (2018), teaching methods and classroom atmosphere could be the reasons contributing to this finding.…”
Section: Levels Of Foreign Language Speaking Anxietysupporting
confidence: 87%
“…Based on the results above, students also mentioned that they are more courageous to speak English as a team rather than individually while speaking in front of the class or many people.The reason is related to their anxiety while speaking in front of many people. The other researcher, Zulfikar (2022), also mentioned that when teachers allow learners to work cohesively in a group and students realize their peers are on their side, they feel less anxious about L2 learning scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fluency can help students feel more self-confident in speaking. Zulfikar (2022) stated that EFL learners tend to have a lower level of fluency due to their lack of exposure to authentic language. To learn to speak English fluently, students need to practice consistently.…”
Section: Introductionmentioning
confidence: 99%
“…According to Al-khresheh and Orak (2021), the immediate correction of students' errors may strike down students' learning motivation. On the contrary, Zulfikar (2022) found that selectively correcting students' errors can effectively decrease students' learning anxiety.…”
Section: Communicative Language Teachingmentioning
confidence: 94%